2014
DOI: 10.14202/vetworld.2014.938-942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of herbal seeds on carcass traits of turkey poults

Abstract: Aim: The present study was conducted to find the effect of four herbal seeds on carcass traits of turkey poults. Materials and Methods:A biological study using Nandanam turkey poults (Meleagris gallapavo) for 8 weeks duration was carried out to evaluate the effect of phytobiotics-containing four herbal seeds influence on production performances like biweekly body weight and on carcass traits. 150 poults were randomly subjected to five dietary treatments in a completely randomized design with basal diet (T1), 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Chicken meat is a common vehicle of food borne illness, Staphylococci mainly S. aureus is the most important causes of food poisoning through enterotoxins (SEs) production and the presence of these organisms has relevant public health implications (Prange et al, 2005 andBhaisare et al, 2014) Most previous studies were interested with coagulase positive S.aureus strains of Staphylococci species as it is still a major cause of food poisoning due to ingestion of enterotoxin (Le Loir, 2003) and the ability to produce such enterotoxin in food is more likely when competing microorganisms were absent, resulting in symptoms of intoxication and common symptoms appear approximately 3-8 hr. after ingestion as nausea, vomiting, abdominal cramps and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken meat is a common vehicle of food borne illness, Staphylococci mainly S. aureus is the most important causes of food poisoning through enterotoxins (SEs) production and the presence of these organisms has relevant public health implications (Prange et al, 2005 andBhaisare et al, 2014) Most previous studies were interested with coagulase positive S.aureus strains of Staphylococci species as it is still a major cause of food poisoning due to ingestion of enterotoxin (Le Loir, 2003) and the ability to produce such enterotoxin in food is more likely when competing microorganisms were absent, resulting in symptoms of intoxication and common symptoms appear approximately 3-8 hr. after ingestion as nausea, vomiting, abdominal cramps and diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…However, Weerasingha and Atapattu (2013) reported that fenugreek seed supplementation had no significant impact on intestinal length per 100g of body weight when measured. In addition, Bhaisare et al (2014) observed that dietary inclusion of Fenugreek seeds at 0.5% level in the eight-week diet of Nandanam Turkey poults resulted in substantial improvement in dressed weight (P<0.05) and attributed it to fenugreek's antimicrobial properties. Contact between digesta and mucosal epithelium might prolong the positive impact on intestinal morphology, which may be more efficient for nutrient absorption (Bogusławska-Tryk et al, 2012).…”
Section: Feed Conversion Ratio (Fcr)mentioning
confidence: 97%
“…Both fenugreek and anise were studied to determine their effect on animal health and performances when used as feed supplementation (10) .…”
Section: Introductionmentioning
confidence: 99%